Observation of the Art and Ideology of the Architectural Gate of the Great Mosque of Jami' Singaraja: Involvement of Hinduism, Islam, and the Kingdom of Buleleng - Luhuringbudi, Teguh; Abdiguno, Panggih; Yani, Achmad (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2024)
This research aims to uncover the complex process of integration and collaboration between the Kingdom of Buleleng, Hinduism and Islam, which is evident in the gate design of the Jami' Singaraja Grand Mosque. The paper uses a logical and concise structure that includes common academic sections, ensuring a clear and necessary flow of information and causal relationships between statements. It uses appropriate vocabulary for the particular subject and adheres to grammatical correctness, conventional structure, clear and logical structure, and balanced judgment. The objective was achieved by using three methods, namely Aditya Wardana's gate architecture method examines the aesthetic nuances and significance of the extrinsic layers associated with the construction of the gate under study, the semiotic method proposed by Riffaterre establishes the implied meaning of the physical form of the gate in question and the ideological method is used to analyze the results of the first two methods to provide a more comprehensive interpretation of the explicit and implied meanings. This study concludes that the gate architecture of the Jami' Singaraja Grand Mosque contributes to the negotiation between environmental sensitivity and the ethics of cultural beauty. This can be observed through three findings a symbol of social status that values responsible pluralism, the obligation to bring joy, maintain expressive values, and dissolve negative elements, a reminder of the guidelines of social life, inner purity, and psychological wisdom; and an ideology of togetherness for the Muslim profile that must pay attention to inclusive personality, mass mobilization for social care, and reproduction of individual piety.